Arrhythmias Occurring in Children during HEMS Intervention: A Retrospective Cohort Study - Piotr Konrad Leszczyński; Arkadiusz Wejnarski; Patryk Rzońca; Angelika Gajowniczek; Robert Gałązkowski; Kryspin Mitura; Daryna Sholokhova (Emergency Medicine International)
Background. Arrhythmias in patients during medical transport remain a challenge for medical personnel. Helicopter emergency medical service (HEMS) crews, as the only medical rescue teams in Poland to conduct rescue flights, keep detailed documentation of monitoring vital functions over short time intervals during the flight. Aims. The aim of this study was to determine the characteristics of cardiac arrhythmia in pediatric patients (up to 12 years of age) transported by HEMS operatives, considering life-threatening rhythms and those that occur during out-of-hospital cardiac arrest (OHCA). Methods. The analysis of HEMS medical documentation covered 90345 missions carried out from 2011 to 2020. Among all activations, 820 cases of arrhythmias in pediatric patients up to 12 years of age were extracted. Results. Missions for males accounted for 60% of all activations (n = 492), while flights for females accounted for 40% (n = 328). A statistically significant relationship between the number of HEMS flights and the season was demonstrated (p=0.015). During the study period, pediatric patients mostly experienced cardiac arrhythmias in the form of supraventricular tachycardia (sVT) (n = 504). Asystole (n = 178) and pulseless electrical activity (PEA) (n = 52) ranked second and third in terms of occurrence, respectively. A statistically significant relationship between the type of heart rhythm disorder and age was demonstrated (p<0.05). Conclusions. Heart rhythm disorders most often affected children between 0 and 3 years of age. As the patient’s age increased, the incidence of arrhythmias decreased. Among pediatric patients, supraventricular tachycardia proved to be the predominant arrhythmia during the study period.